Sexual Behavior and Semen Quality of Crossbred Bulls after Supplementation of Flaxseed and with Rubber Mat Floor - Ali, Samir Humeida; Mohanty, Tushar Kumar; Sinha, Ranjana; Singh, Pawan; C, Kotresh Prasad; Bhakat, Mukesh; Panchabai, Girish (Indian Journal of Veterinary Sciences and Biotechnology, 2021)
The experiment was conducted to study the effect of dietary supplementation of flaxseed and bedding material on sexual behavior, libido, and semen quality of crossbred bulls. For this, seventeen mature healthy breeding bulls were assigned to three groups as G1, G2, and G3 with 6, 5, 6 bulls, respectively. The bulls of G1 were fed as per standard diet (ICAR, 2013) and served as control. Bulls of G2 were fed as per standard diet G1 plus roasted flaxseed @ 1 kg/bull/day for 120 days, and bulls of G3 were provided rubber mat as bedding material and fed as per G2. The libido of the bulls was assessed by sexual behavior parameters and hormonal profile, and the seminal quality was examined. Significant (P <0.05) changes were observed in sexual behavior of both the treatment groups as compared to control. Semen ejaculate volume, sperm concentration and total sperm output per ejaculate did not differ among the groups. Improved semen quality parameters, viz., sperm motility, viability, morphology, and HOST reactivity were observed in the bulls supplemented with flaxseed and provided rubber bedding material. Testosterone, Luteinizing Hormone (LH), and estradiol hormones did not show any difference among the groups. It can be concluded that the dietary supplementation of roasted flaxseed alone and along with bedding material during winter season improved sexual behavior, libido, and the semen quality of crossbred bulls.